Menelaah Pemikiran Ibn Rusyd Dalam Kitab Fasl al-Maqāl fi Mā Baina al-Hikmah wa al-Syari‘ah min al-Ittisāl - Muh. Bahrul Afif (El-Afkar: Jurnal Pemikiran Keislaman dan Tafsir Hadis, 2019)
This article, particularly, discusses about the points of Ibn Rusyd thought in his work entitled Faṣl al-Maqāl Fīmā Baina al-Ḥikmah wa al-Syarī‘ah min al-Ittiṣāl. This work is one of the original and important works belonging to Ibn Rusyd, besides of his other three main works, namely al-Kasyf ‘an Manāhij al-Adillah fī ‘Aqāid al-Millah, Tahāfut al-Tahāfut and Bidāyah al-Mujtahid wa Nihāyah al-Muqtaṣid. Faṣl al-Maqāl was written by him as a response to the intellectual condition in his era, that was the war of thought (gazwah al-fikr) between a group that rejected philosophy, that was spearheaded by jurisprudence experts (fuqahā’) and a group of philosophers. Hence, Ibn Rusyd as a supreme judge (qāḍī al-quḍāt) at that moment, felt the need to reconcile them by showing that there was no opposition and there was nothing to contradict between religion and philosophy. This work was also intended to purify the philosophical thought of Aristoteles. There are three points of Ibn Rusyd thought in Faṣl al-Maqāl: first, reconciling between philosophy and syari’ah; second, ta’wil as a method that was offered by him to find the common ground of the two entities; third, explanation about the central issues that become the reason for the conflict between philosophers and a group that rejected philosophy. From the explanations of Ibn Rusyd, it seemed that he was affected by the other figures like Aristoteles and the early Muslim philosophers. Some of the issues contained in this book are also commented and criticized by the authorities or scholars who studied Ibn Rusyd thought.